سيميولوجيا الشخصيات في الحكاية الشعبية بمنطقة الغرب الجزائري - براهمي, سعدية (كلية الأدب العربي والفنون, 2024)
بما أنّ الحكاية الشعبيّة جزء من تراثنا العريق المعبّر عن هويتنا، وجب علينا دراسته حفاظا عليه، نظرا لأهميته، فجاء هذا البحث المعنون بـ "سيميولوجيا الشّخصيات في الحكايات الشعبيّة بمنطقة الغرب الجزائريّ للتعرّف على وظائفها وأبعادها، وفق الخطّة التالية، جانب نظري تعرّفنا فيه على الحكايةالشعبيّة بأنواعها، فرؤية فلاديمير بروب وفيليب هامون للشّخصية، وجانب تطبيقي تمّ الإجابة فيه على مدى تطويع حكاية "الضاوية وأحمد" لآليات المذهب المورفولوجيلبروب، ودراسة مدى فعالية تطبيق تصنيف هامون للشخصيات في بعض الحكايات الشعبيّة بمنطقة الغرب الجزائريّ وقد خلصت الدراسة إلى تواجد معظم وظائف الشخصيةالتي أقرّها بروب، وأبعادها وفق تصنيفات هامون Since the folktale is part of our ancient heritage that expresses our identity, we must study it in order to preserve it, given its importance. This research, entitled “The Semiology of Characters in Folktales in the Western Algerian Region, came to identify their functions and dimensions, according to the following plan, a theoretical aspect in which we learned about the story.” Folklore of all kinds, the vision of Vladimir Propp and Philip Hamon for character, and an applied aspect in which the answer was given to the extent to which the story of “Al-Daouia and Ahmed” adapts the mechanisms of Propp’s morphological doctrine, and a study of the effectiveness of applying Hamon’s classification of characters in some popular tales in the western Algerian region. The study concluded that most of the character’s functions are present. Which was approved by Propp, and its dimensions are according to Hamon's classifications.
Keywords: سيميولوجيا، الحكاية الشعبيّة، التحليل المورفولوجي، الضاوية; semiology, folk tale, morphological analysis,Aldaouia.